A Phylogenetic Study of the Concept of Celestial Orb - Mohammad Mahdi Sadrforati; Amir-Mohammad Gamini (Principia: An International Journal of Epistemology, 2022)
This paper presents a phylogenetic study of the concept of orb from its rise to its abandonment. While a heavy load of literature is dedicated to the introduction and abandonment of the concept, there are few systematic studies on the semantic components of this concept in the Islamic tradition of astronomy. We will investigate conceptual articulation among Arab astronomers by distinguishing the astronomical and philosophical understandings of the concept. While the former mainly focuses on the empirical evidence, the latter emphasizes causal and physical role of the concept’s referent. Such a distinction enables us to characterize some key conceptual components of the concept of orb. Among other components articulated by the Arab astronomers, the hardness of orbs, led Tycho Brahe and his fellow astronomers to abandon the concept.